Handbook of antiblocking, release, and slip additives - Wypych, George (ChemTec Publishing, 2021)
"This handbook is the first-ever book written on the subject of antiblocking, release, and slip additives, which are of high industrial importance. The fourth edition has included all new information that became available in the last 7 years since the publication of the last edition. Thirty chemical families form a core of industrial developments, which resulted in a large number of commercial products used by industry as antiblocking, release, and slip additives. These additives are used in the production of materials from 44 families of polymers, rubbers, and natural products. Polymers containing antiblocking, release, and slip additives are processed by 18 groups of processing methods. The processing methods are used by almost 30 industries."--